Predicting the Origins of Anti-Blood Group Antibody Specificity: A Case Study of the ABO A- and B-Antigens - Makeneni, Spandana; Ji, Ye; Watson, David C.; Young, N. Martin; Woods, Robert J. (Frontiers in Immunology, 2014)
The ABO blood group system is the most important blood type system in human transfusion medicine. Here, we explore the specificity of antibody recognition towards ABO blood group antigens using computational modeling and biolayer interferometry. Automated docking and molecular dynamics (MD) simulations were used to explore the origin of the specificity of an anti-blood group A antibody variable fragment (Fv AC1001). The analysis predicts a number of Fv-antigen interactions that contribute to affinity, including a hydrogen bond between a HisL49 and the carbonyl moiety of the GalNAc in antigen A. This interaction was consistent with the dependence of affinity on pH, as measured experimentally; at lower pH there is an increase in binding affinity. Binding energy calculations provide unique insight into the origin of interaction energies at a per-residue level in both the scFv and the trisaccharide antigen. The calculations indicate that while the antibody can accommodate both blood group A and B antigens in its combining site, the A antigen is preferred by approximately 4 kcal/mol, consistent with the lack of binding observed for the B antigen.